Motility and chemotaxis mediate the preferential colonization of gastric injury sites by Helicobacter pylori. - Eitaro Aihara; Chet Closson; Andrea L Matthis; Michael A Schumacher; Amy C Engevik; Yana Zavros; Karen M Ottemann; Marshall H Montrose (PLoS Pathogens, 2014)
Helicobacter pylori (H. pylori) is a pathogen contributing to peptic inflammation, ulceration, and cancer. A crucial step in the pathogenic sequence is when the bacterium first interacts with gastric tissue, an event that is poorly understood in vivo. We have shown that the luminal space adjacent to gastric epithelial damage is a microenvironment, and we hypothesized that this microenvironment might enhance H. pylori colonization. Inoculation with 106 H. pylori (wild-type Sydney Strain 1, SS1) significantly delayed healing of acetic-acid induced ulcers at Day 1, 7 and 30 post-inoculation, and wild-type SS1 preferentially colonized the ulcerated area compared to uninjured gastric tissue in the same animal at all time points. Gastric resident Lactobacillus spp. did not preferentially colonize ulcerated tissue. To determine whether bacterial motility and chemotaxis are important to ulcer healing and colonization, we analyzed isogenic H. pylori mutants defective in motility (ΔmotB) or chemotaxis (ΔcheY). ΔmotB (10(6)) failed to colonize ulcerated or healthy stomach tissue. ΔcheY (10(6)) colonized both tissues, but without preferential colonization of ulcerated tissue. However, ΔcheY did modestly delay ulcer healing, suggesting that chemotaxis is not required for this process. We used two-photon microscopy to induce microscopic epithelial lesions in vivo, and evaluated accumulation of fluorescently labeled H. pylori at gastric damage sites in the time frame of minutes instead of days. By 5 min after inducing damage, H. pylori SS1 preferentially accumulated at the site of damage and inhibited gastric epithelial restitution. H. pylori ΔcheY modestly accumulated at the gastric surface and inhibited restitution, but did not preferentially accumulate at the injury site. H. pylori ΔmotB neither accumulated at the surface nor inhibited restitution. We conclude that bacterial chemosensing and motility rapidly promote H. pylori colonization of injury sites, and thereby biases the injured tissue towards sustained gastric damage.